ANALYSIS OF FACTORS INFLUENCING DECISIONS TO VISIT ADNA STUDIO SURABAYA VOL. LE MUSÉE - Junko Alessandro Effendy; Alma Rizky Arrazandi; Linda Laurensia Soetandio (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
The increasing business in the creative industry can be seen from one of the new art galleries in the city of Surabaya called Adna Studio. This art gallery won 3,000 visitors in November 2021 with the theme of the first volume called Le Musèe. This study was conducted to determine the factors that reflected the decision to visit Adna Studio Surabaya, by distributing questionnaires to 97 respondents aged 18-35 years with the criteria of having visited the Adna Studio Creative art gallery vol. Le Musèe. Sampling in this study was carried out by purposive sampling method, besides that the method in this study was factor analysis which grouped these factors into dominant factors that reflected the decision to visit. The results of this study indicate that the dominant factors that influence the decision to visit are the theme, intrinsic motivation and atmosphere. There are variables that are not accepted, namely location variables and social influences. Therefore, the management must pay more attention to maintenance and innovate through various activities at the Adna Studio Surabaya art gallery.